PENDAMPINGAN PEMBUKUAN DANTATA KELOLA KEUANGAN YANG BAIK DI COLUMBARIUM, KEVIKEPAN DAERAH ISTIMEWA YOGYAKARTA - Anggraini, Fr Reni Retno; Karsana, Yusef Widya; Siswanto, FA Joko; Marianti, Maria Merry; Kristanto, Agustinus Tri; Sinaga, Klemensia Erna Christina (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to help partners manage financial transaction books so that they have good financial governance. Partners in this service are the Management of the Paguyuban Sukma Sinukarta Jogjakarta. In general, the method of implementing this service is by assisting with financial bookkeeping and financial governance administration. The steps in the service are holding discussions with community association administrators, exploring problems in the bookkeeping of financial transactions and good governance, providing assistance in preparing financial reports and accountability, and holding discussions with administrators to evaluate the good financial management of the Columbarium. The result of the service is that the management can keep books of financial transactions and have good financial governance. The management can maintain and provide services regarding financial information to people whose families are buried in the Columbarium.